Sustainable Tourism Business Promotion in Pakistan: A Descriptive Analysis of Logistics and Environmental Agreements - ULLAH, Nazir; AZIZ, Saidatul Nadia Abd; IDREES, Rao Qasim (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.11.7(47).13, 2020)
The tourism industry is considered most important aspect for the progress of the economy as well as enhancing employment rate of the country. Tourism sector comprises on different activities such as, hotels, restaurants, tour operators, transportation management and providing services to the local and foreign clients at their destinations. Furthermore, tourism industry is also very important to bring foreign currency in the country through the visitors which consequently enhance the foreign reserves. However, there is deficiency of prescribed rules and regulations for Pakistan tourism sector particularly environmental agreements and their enforcement consequently it creates many operational as well as market-based issues, hence drops the progress rate of this sector. Pakistan is also one of those countries where tourism business and services are being dealt without any proper regulatory system and it can further disturb the tourism investment by the Chinese or domestic investors under CPEC projects. There is strong connection between tourism business development and better logistics infrastructure and facilities of roads and railway sectors. This research article provides an analysis of tourism development in Pakistan through well planed physical infrastructure in order to get better results from tourism investments. In this article, authors adopt descriptive approach while providing the information and also explore the benefits and utilisation of CPEC overland logistics investment by the Chinese companies in tourism industry. There is an analytical jurisprudence approach is applied to highlight logistics benefits and preferences between China and Pakistan as well as the changes in environmental agreements. This study concludes that better logistics and transport infrastructure along with comprehensive environmental policies further accelerates tourism business with major trade markets in the country. Positive rearrangement of environmental agreements as well as logistics and transport is helpful to attract foreign investment in the tourism industry and particularly in areas which probably would have capacity to generate revenue. In this manner, tourism sector through developed connectivity and growth of infrastructure creates employment opportunities in the country.